The Impact of Augmented Reality Learning Media on Enhancing Knowledge and Skills in Midwifery Students: A Literature Review - Nurwaridha, Nurwaridha; Ahmad, Mardiana; Syarif, Syafruddin; Idrus, Hasta Handayani (Journal of Neonatal Surgery, 2025)
Background: The rapid development of digital learning tools has led to the integration of augmented reality (AR) into healthcare education, including midwifery training. AR offers interactive and immersive learning experiences that enhance both theoretical knowledge and practical skills. However, the effectiveness of AR in midwifery education remains a subject of ongoing research. Objectives: This study aims to evaluate the impact of augmented reality learning media on improving knowledge and skills among midwifery students through a literature review approach. Methods: A literature review was conducted using national and international journals published between 2019 and 2024. The databases searched included Google Scholar, Semantic Scholar, PubMed, and ScienceDirect. The search was performed using the keywords “Augmented Reality in midwifery,” “Knowledge and skills,” and “Intravenous training.” A total of 164 articles were retrieved, and after applying filters for publication year, abstract relevance, full-text availability, and research type, 30 relevant studies were selected for final analysis. Results: The findings indicate that AR-based learning media significantly improve midwifery students’ knowledge retention and procedural skills. The interactive nature of AR enhances student engagement, allowing better visualization of anatomical structures and simulation of clinical procedures, particularly in intravenous insertion and labor management. Several studies also highlight the positive effects of AR in reducing errors and increasing confidence during skill application. Conclusion: Augmented reality is a promising educational tool that enhances knowledge acquisition and practical competencies in midwifery students. Its integration into midwifery curricula could serve as an innovative approach to bridging the gap between theoretical learning and clinical practice. Further research is recommended to explore long-term effects and best implementation strategies.